Statin use and survival after colorectal cancer: the importance of comprehensive confounder adjustment - Hoffmeister, Michael; Tóth, Csaba; Kloor, Matthias; Roth, Wilfried; Bläker, Hendrik; Chang-Claude, Jenny; Brenner, Hermann (Journal of the National Cancer Institute, 2015)
Statins have been associated with moderate reductions in mortality among colorectal cancer (CRC) patients, but these studies lacked adjustment for some potentially relevant factors associated with statin use. We aimed to provide more detailed results on this association from a population-based patient cohort study.Use of statins and other risk or protective factors were assessed in standardized interviews with 2697 patients from southern Germany with a diagnosis of incident CRC between 2003 and 2009 (Darmkrebs: Chancen der Verhütung durch Screening [DACHS] study). Follow-up included assessment of therapy details, recurrence, vital status, and cause of death. Information about molecular pathological subtypes of CRC was available for 1209 patients. Cox proportional hazard regression models were used to estimate adjusted hazard ratios (HRs) and their 95% confidence intervals (CIs). All statistical tests were two-sided.Patients were age 68 years on average, 412 used statins (15%), and 769 died during follow-up (29%). After a median follow-up time of 3.4 years, use of statins was not associated with overall (HR = 1.10, 95% CI = 0.85 to 1.41), CRC-specific (HR = 1.11, 95% CI = 0.82 to 1.50), or recurrence-free survival (HR = 0.90, 95% CI = 0.63 to 1.27). Analyses in relevant subgroups also showed no association of statin use with overall and CRC-specific survival, and no associations were observed after stratifying for major pathological subtypes. Among stage I and II patients, statin use was associated with better recurrence-free but not with better CRC-specific survival.Statin use was not associated with reduced mortality among CRC patients. Effects reported in previous studies might reflect incomplete control for stage at diagnosis and other factors associated with the use of statins.
Gesehen am 29.10.2024